2003
DOI: 10.1099/mic.0.26451-0
|View full text |Cite
|
Sign up to set email alerts
|

In situ localization of manganese peroxidase production in mycelial pellets of Phanerochaete chrysosporium

Abstract: The ultrastructure of Phanerochaete chrysosporium hyphae from pellets in submerged liquid cultures was investigated in order to learn more about the interrelation between fungal architecture and manganese peroxidase (MnP) production. At day 2 of cultivation, some subapical regions of hyphae in the outer and middle zones of the pellet initiated differentiation into intercalary thick-walled chlamydospore-like cells of about 10 mm diameter. At the periphery of the cytoplasm of these cells, a large number of mitoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…It can be concluded that LiP seems to be excreted on the pellet surface where probably most of the hyphal tips are present. This datum is in agreement with previous works using P. chrysosporium where it was speculated that peroxidases are excreted through the apex of secondary growing hyphae (Moukha et al 1993) or by autolysis of chlamydospore-like cells present in outer or middle zones of the pellets (Jimé nez- Tobon et al 2003).…”
Section: Resultssupporting
confidence: 92%
“…It can be concluded that LiP seems to be excreted on the pellet surface where probably most of the hyphal tips are present. This datum is in agreement with previous works using P. chrysosporium where it was speculated that peroxidases are excreted through the apex of secondary growing hyphae (Moukha et al 1993) or by autolysis of chlamydospore-like cells present in outer or middle zones of the pellets (Jimé nez- Tobon et al 2003).…”
Section: Resultssupporting
confidence: 92%
“…The emerging regulatory elements of autolysis provide us with good opportunities to control and manipulate this process for several practical proposes. In the fermentation industry, induction of autolysis can accelerate the release of certain intracellular metabolites [1,7] and enhance the production of numerous industrially important hydrolases including proteinases, chitinases, and glucanases [1] and other enzymes [8]. Inhibition of autolysis can also help us to lengthen the idiophase of industrial cultivations, can maintain pelleted cell morphology as well as can hinder or even block proteinase production and, hence, proteolytic degradation of valuable protein products [1,4].…”
Section: Introductionmentioning
confidence: 99%
“…Intermediate values would be useful to determine in order to establish if any correlation exists between laccase activity and phenolics degradation. It was for example shown that ligninolytic enzymes may be sensitive to proteases produced by different WRF strains during their growth cycle (Jimenez-Tobon et al 2003). Although, apparently not detected in the present investigation (not illustrated), the role of other enzymes, including Lignin peroxidase, Manganese peroxidase (Kondo et al 1994;Belinky et al 2003;Songulashvili et al 2007) and cellobiose dehydrogenase should be also evaluated in more details.…”
Section: Discussionmentioning
confidence: 99%